2016
DOI: 10.1016/j.ejps.2015.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating unwanted amorphisation: A screening method for the selection of suitable excipients

Abstract: Co-processing an active pharmaceutical ingredient (API) with a low Tg excipient has been previously reported to be an effective strategy for preventing drug amorphisation on milling.This technique relies on the ability of the excipient to form a molecular dispersion with the amorphous API during the milling process. The presence of the excipient within the amorphous phase induces a reduction of the Tg. Hence, the molecular dispersion becomes less stable than the amorphous API alone and recrystallises upon mill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…In some early reports, one can find that a high- T g matrix does not necessarily guarantee the greater physical stability of the amorphous systems. , The molecular factors, involving hydrogen bonding, ionic interactions, steric hindrances, and so on, can also affect the overall crystallization tendency of the coamorphous mixtures. ,, Here, it is worthy to mention the plasticization effect, which is always associated with reduced T g values, enhanced molecular mobility, and eventually facilitated crystallization . Nevertheless, it has also been reported in the literature that a low- T g polymer, such as poly­(ethylene oxide) (PEO), could exert selective accelerating effects on the crystallization kinetics of different polymorphs of indomethacin (IMC) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some early reports, one can find that a high- T g matrix does not necessarily guarantee the greater physical stability of the amorphous systems. , The molecular factors, involving hydrogen bonding, ionic interactions, steric hindrances, and so on, can also affect the overall crystallization tendency of the coamorphous mixtures. ,, Here, it is worthy to mention the plasticization effect, which is always associated with reduced T g values, enhanced molecular mobility, and eventually facilitated crystallization . Nevertheless, it has also been reported in the literature that a low- T g polymer, such as poly­(ethylene oxide) (PEO), could exert selective accelerating effects on the crystallization kinetics of different polymorphs of indomethacin (IMC) .…”
Section: Introductionmentioning
confidence: 99%
“…10,17,18 Here, it is worthy to mention the plasticization effect, which is always associated with reduced T g values, enhanced molecular mobility, and eventually facilitated crystallization. 19 Nevertheless, it has also been reported in the literature that a low-T g polymer, such as poly(ethylene oxide) (PEO), could exert selective accelerating effects on the crystallization kinetics of different polymorphs of indomethacin (IMC). 20 Moreover, our recent work found that the crystallization of amorphous nifedipine (NIF, T g = 317 K and with a large tendency to recrystallize from the supercooled state) can be effectively suppressed by its structural analogue, nimodipine (NIM, T g = 289 K), at both ambient and elevated pressures, indicating that the plasticizers might be also useful in stabilization of the amorphous APIs.…”
Section: ■ Introductionmentioning
confidence: 99%
“…15−18 Yet, understanding these transformations is of practical value for the pharmaceutical industry. Controlling the milling process would prevent the formation of undesired physical states 19 (poorly soluble crystalline forms, unstable amorphous substances, etc.) and establish innovative and suitable formulations enabling pharmaceutical ingredients to be placed into therapeutically efficient states.…”
Section: ■ Introductionmentioning
confidence: 99%
“…High-energy milling, for all those reasons, is a valuable candidate to become an efficient manufacturing method of amorphous substances, preserving the chemical completeness when it is not accompanied by excessive heating. Although observed in numerous compounds of pharmaceutical interest, phase transformations upon milling have still not been investigated thoroughly to rationalize experimentally encountered situations. Yet, understanding these transformations is of practical value for the pharmaceutical industry. Controlling the milling process would prevent the formation of undesired physical states (poorly soluble crystalline forms, unstable amorphous substances, etc.) and establish innovative and suitable formulations enabling pharmaceutical ingredients to be placed into therapeutically efficient states .…”
Section: Introductionmentioning
confidence: 99%
“…Without an obvious sign of recrystallization, the diacids with relatively low T g s, i.e., MAE (4.6 • C) and MAL (−20 • C), on the other hand, resulted in Class III GFA behavior [16,40]. It has been shown that for co-milling and spray-drying, which are also major sources of inducing amorphization, high T g excipients confer functional advantages for stabilizing the amorphous drugs [41][42][43][44][45]. However, the opposite trend was observed in our study, i.e., the crystallization tendency was positively correlated with the T g of the coformer (Figure 2).…”
Section: Role Of C4 Diacid Coformers In Altering the Glass-forming Abmentioning
confidence: 99%